aerial photographic interpretation for population estimation and its distribution: A Case Study in Kalianda and Palas Subdistricts, South Lampung Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1984)
Population data based on a census is the most reliable one. The census is. however, carried out every ten years. Data in the intercensal period is mainly based on population registration or population survey. Air photos are used in this research as a case study for the probable method of providing population data in the intercensal period. Two subdistricts (Kalianda and Palas) in South Lampung Regency are taken as studied area. There are three types of population data which can be extracted from air photos, i.e.: the number of population, population increase, and population distribution. Besides. the village boundary lines can be extracted as well. It is used to provide data on the distribution of population. The number of population is acquired in two ways. i.e.: (1) multiplying the number of dwelling house (R) and the average number of people in each house (r), and (2) multiplying the settlement area (L) and the population density in the settlement area (k). R.P. and L. K. are compared to the number of population based on complete enumeration in the field. Population data based on population registration are also compared to the enumerated data. Using air photos scaled to 1:20,000. L50.000, and 1:100.000. the estimated population differ in 4.48% up to 9.17% from the enumerated data. It is better than the registration data which differ 9.47% up to 49.70% from the field enumerated data. Aerial photographs are the best tool in providing population distribution because dwelling houses and settlement areas are well presented in their spatial distribution. The population increase is hard to be traced in this research -because of the scale inequality of the available photographs. It is hard to compare features on 1:100,000 air photos with that on 1:20,000 ones. Village boundary lines can be traced with notable ease because it consists of discernable features. such as lane, footpath, dikes, irrigation channel. etc.